Odpowiedź:
1)
(jeśli pod liczbą jest minus to znaczy że to potęga bo nie wiem jak inaczej to zapisać lecz mam nadzieje że pomogłem)
a) -x+4y = -3+4*(-5) = -3+(-20) = -23
b) 4b2 - a(2b + 1) = 4*(-2)2 - 3(2*(-2) +1) = 4*4 - 3(-4 + 1) = 16-3-4 = 9
- -
2)
2,5xy3 * (-1,4) * xy2 = -3.5x2y4
- - - -
3)
4x2 - 7y + 2x2 + 7y + 1 = 6x2 + 1
- - -
4x2 +2x2 = 6x2
- - -
-7y + 7y = 0y
Odp. C
4)
Nie Wiem
5)
a) 6a - 4 + 2a + 7 - 5a + 1 = 3*(-3) + 4 = -9 + 4 = -5
6a + 2a - 5a = 3a
-4 + 7 + 1 = 4
b) 4x + 2y + 5 - 5x +3y =-1*2 + 5 + 5*(-0,4) = -2 + 5 +(-2) = 1
4x - 5x = -1x
2y + 3y = 5y
6)
Nie Wiem
Szczegółowe wyjaśnienie: